ANALISIS PEMERATAAN PENDAPATAN ANTAR WILAYAH KECAMATAN DI KABUPATEN SEMARANG - Nanang Yusroni; Umar Chadhiq (Universitas Wahid Hasyim, 2008)
Regional development in Semarang Regent as integral part of national development, was held for human development, which directed to regional economic development with priority and potency adjustment. In Semarang regent there was high discrepancy , near to 1 or average 0,66. It meant passing of critical number 0,5.From sector number based on LQ value, the leading sectors on Semarang Regent were : industry, electric power, gas and water, trade, hotel and restaurant, distribution and communication, and service. With harmony of regional and sector approach which was implemented on development policy, could give real result in economic growth trigger and product domestic regional brutto each of district, utility on economic potency Key words : Product domestic regional brutto, LQ index. Economic growth